Writing the New World The Politics of Natural History in the Early Spanish Empire - Caraccioli, Mauro José (University Press of Florida, 2021)
In Writing the New World, Mauro Caraccioli examines the natural history writings of early Spanish missionaries, using these texts to argue that colonial Latin America was fundamental in the development of modern political thought. Revealing their narrative context, religious ideals, and political implications, Caraccioli shows how these sixteenth-century works promoted a distinct genre of philosophical wonder in service of an emerging colonial social order.Caraccioli discusses narrative techniques employed by well-known figures such as Gonzalo Fernández de Oviedo and Bartolomé de Las Casas as well as less-studied authors including Bernardino de Sahagún, Francisco Hernández, and José de Acosta. More than mere catalogues of the natural wonders of the New World, these writings advocate mining and molding untapped landscapes, detailing the possibilities for extracting not just resources from the land but also new moral values from indigenous communities. Analyzing the intersections between politics, science, and faith that surface in these accounts, Caraccioli shows how the portrayal of nature served the ends of imperial domination.Integrating the fields of political theory, environmental history, Latin American literature, and religious studies, this book showcases Spain's role in the intellectual formation of modernity and Latin America's place as the crucible for the Scientific Revolution. Its insights are also relevant to debates about the interplay between politics and environmental studies in the Global South today.